Analysis of mathematical functions using the first and second derivatives in students of Mathematics and Physics at UNHEVAL - Paragua-Morales, Melecio (2021)
The purpose of the study was to test the effectiveness of the application of the first and second derivatives to analyze the mathematical functions in future teachers of Mathematics and Physics at UNHEVAL; for this, a cause-effect study and quasi-experimental design was carried out, hoping to optimize the learning of functions in a graphical and analytical way, by means of the exact location of the maximum and minimum points, inflection, determination of the concavity up and down, and others; we worked with a sample of 114 students, of them 73 units of analysis were control and 41 experimental; the data were collected with the written evaluative test, and they were processed obtaining descriptive statistics that allowed to say that the value Z = 7,09 is higher with respect to the critical z = 1,96 at 95% reliability, which allowed to reject the null hypothesis and accept the research hypothesis, because it allows to improve the apprehension of the theory and practice, with the analysis of functions applying the derivatives in the future teachers of mathematics and physics at UNHEVAL.